Estudo e implementação de uma fonte chaveada empregando controle baseado em passividade, para alimentação de amplificadores de potência de áudio - Thiago Ribeiro de Oliveira (2011)
Due to the request of the audio market for more efficient and compact systems, the technology applied to audio power amplification systems has seen over the past decades a significant evolution. Gradually, the commonly used linear power amplifier topologies are losing space to the more advanced switched-mode designs. However, despite the effortssurrounding the improvement of the performance and efficiency of the amplification equipments, the power supplies used in the power stage are still mostly based on unregulated bulky topologies. In this work, a study about the interaction between the power supply and the audio power amplifier was conducted aiming to identify the factors and events that affect the behavior and performance of the power supply. The investigations were headed towards the definition of the load perturbation profile, which is imposed to the power supply by the amplifiers operation, and its relation to the ripple at the power supply voltage rails. The defined relation was then used to evaluate the performance of unregulated power supplies and switched converters controlled by linear and assivity-based nonlinear strategies.